Enhancement of optical transmittance and electrical resistivity of post-annealed ITO thin films RF sputtered on Si - Ali, Ahmad Hadi; Hassan, Zainuriah; Shuhaimi, Ahmad (Elsevier, 2018)
This paper reports on the enhancement of optical transmittance and electrical resistivity of indium tin oxide (ITO) transparent conductive oxides (TCO) deposited by radio frequency (RF) sputtering on Si substrate. Post-annealing was conducted on the samples at temperature ranges of 500–700 °C. From X-ray diffraction analysis (XRD), ITO (2 2 2) peak was observed after post-annealing indicating crystallization phase of the films. From UV–vis measurements, the ITO thin film shows highest transmittance of more than 90% at post-annealing temperature of 700 °C as compared to the as-deposited thin films. From atomic force microscope (AFM), the surface roughness becomes smoother after post-annealing as compared to the as-deposited. The lowest electrical resistivity for ITO sample is 6.68 × 10 −4 Ω cm after post-annealed at 700 °C that are contributed by high carrier concentration and mobility. The improved structural and surface morphological characteristics helps in increasing the optical transmittance and reducing the electrical resistivity of the ITO thin films.